2005
DOI: 10.1116/1.1924424
|View full text |Cite
|
Sign up to set email alerts
|

High quality AlSb bulk material on Si substrates using a monolithic self-assembled quantum dot nucleation layer

Abstract: We report and characterize the growth of defect-free AlSb bulk material on Si (001) substrates using a monolithic self-assembled AlSb quantum dot (QD) nucleation layer. During the first few monolayers of AlSb growth on Si, highly crystalline QDs form. With continued deposition, the islands coalesce into a planar material with no detectable defects. The QD nucleation layer facilitates a completely relaxed AlSb within ∼100 ML of deposition according to x-ray diffraction. We attribute the success of AlSb growth o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…The coalescence of islands may lead to non-uniform relaxation and induce additional defects. Nevertheless, for some material systems an initial noticeable island-like III/V nucleation was successfully applied [72][73][74]. Inter-diffusion of the group IV and III/V atoms on the short [75] as well as on the long range has a strong impact on the layer properties and can lead to unintentional doping.…”
Section: Si Surface Preparation and Iii/v Nucleationmentioning
confidence: 99%
“…The coalescence of islands may lead to non-uniform relaxation and induce additional defects. Nevertheless, for some material systems an initial noticeable island-like III/V nucleation was successfully applied [72][73][74]. Inter-diffusion of the group IV and III/V atoms on the short [75] as well as on the long range has a strong impact on the layer properties and can lead to unintentional doping.…”
Section: Si Surface Preparation and Iii/v Nucleationmentioning
confidence: 99%
“…The RHEED and AFM analysis of the early stages of AlSb growth on Si indicate that AlSb epilayers also form islands on Si or GaAs substrates, [7][8][9][10][11] which are denser and coalesce at significantly lower thicknesses as compared to GaSb. 12 It has also been observed that introducing a thin buffer layer of AlSb can significantly improve the quality of GaSb films by accelerating the plateau-like growth of GaSb among AlSb islands.…”
Section: Introductionmentioning
confidence: 99%
“…III/Sb tends to nucleate easily as three-dimensional islands on a Si surface [20,50,51], even at low growth temperatures. A further reduction in growth temperature to improve the wetting behavior leads to a diminishing growth rate, whereas a higher material flux into the chamber can cause selectivity issues on the oxide pattern [38].…”
Section: Defect Density In Gasb Nano-ridgesmentioning
confidence: 99%